Synthesis, Characterization, and Osteoblastic Cell Culture of Poly(L-co-D,L-lactide-co-trimethylene carbonate) Scaffolds - Messias, André Dutra; Martins, Kelly Fernanda; Motta, Adriana Cristina; Duek, Eliana Aparecida de Rezende (International Journal of Biomaterials, 2014)
Lactide-based polymers have been widely investigated as materials for tissue engineering. However, characteristics such as low flexibility and elongation tend to limit particular applications, although these can be enhanced by adding plasticizers such as trimethylene carbonate (TMC) to the polymer chain of the copolymer poly(L-lactide-co-D,L-lactide) (PLDLA). The aim of this work was to synthesize and characterize a terpolymer of L-lactide, D,L-lactide, and TMC. The polymers were synthesized from 30% TMC by bulk polymerization and resulted in an average molar mass >105 g/mol. Thermal investigation of PLDLA-TMC showed a decrease in the glass transition and onset temperatures compared to PLDLA. PLDLA-TMC scaffolds stimulated the proliferation and normal phenotypic manifestations of cultured osteoblasts. These results show that it was possible to produce a terpolymer from L-lactide, D,L-lactide, and TMC. Scaffolds of this terpolymer had important characteristics that could be useful for applications in bone tissue engineering.